Report of the 23rd meeting on signal transduction 2019: trends in cancer and infection - Schirmer, Bastian; Giehl, Klaudia; Hieke-Kubatzky, Katharina (International journal of molecular sciences, 2020)
The annual meeting “Signal Transduction–Receptors, Mediators and Genes” of the Signal Transduction Society (STS) is an interdisciplinary conference open to all scientists sharing the common interest in elucidating the signalling pathways underlying the physiological or pathological processes in health and disease of humans, animals, plants, fungi, prokaryotes and protists. The 23rd meeting on signal transduction was held from 4–6 November 2019 in Weimar, Germany, and focused on “Trends in Cancer and Infection”. As usual, keynote presentations by invited scientists introduced the respective workshops and were followed by speakers chosen from the submitted abstracts. Ample time had been reserved for discussion of the presented data during the workshops. In this report, we provide a concise summary of the various workshops and further aspects of the scientific program.
Gesehen am 22.03.2021